Self‐Powered Cursor Using a Triboelectric Mechanism. Issue 7 (28th May 2018) - Wu, Han; Shi, Qiongfeng; Wang, Fei; Thean, Aaron Voon‐Yew; Lee, Chengkuo
Abstract: This work reports the complete theoretical modeling, simulation, and experimental characterization of a self‐powered cursor based on triboelectric nanogenerator (TENG). The self‐powered cursor is made of liquid‐metal and polydimethylsiloxane (PDMS) mixture that deforms and contacts with different sensing electrodes under different applied force. The self‐powered cursor has the capability of simultaneously detecting normal force (0–25 N) and shear force direction (0°–360°) for the first time. The normal force sensing is characterized by open‐circuit voltage, charge, and current with the sensitivity of 0.131 V N −1, 0.048 nC N −1, and 0.175 nA N −1, respectively. The shear force direction detection can achieve a direction resolution of 15°. Because of the high output voltage and low internal impedance, the self‐powered cursor is readily compatible with commercial portable circuits without the requirement of specified bulky high‐impedance instruments to detect the output voltage. Demonstration of the self‐powered cursor as a triggering signal to drive a small vehicle is successfully realized by directly detecting the output voltage without any periphery signal processing circuits. The robust structure, stable output performance, and self‐powered sensing property enable the self‐powered cursor as an ideal human machine interface towards batteryless, energy saving, and environmentally friendly applications. Abstract : A self‐powered cursor based on a triboelectric mechanism is proposed to detect both the normal force and shear force. The robust structure, stable output performance, and self‐powered nature of the device enable it as an ideal human machine interface for smart control and batteryless internet‐of‐things (IoT) applications.